Comparison of three-point belt fit between humans and Hybrid-III anthropometric test devices in a driver mockup. (2nd January 2020) - Park, Jangwoon; Ebert, Sheila M.; Reed, Matthew P.; Hallman, Jason J.
Abstract: Objective: The Hybrid-III anthropometric test devices (ATDs) are widely used by the automotive industry to evaluate restraint system performance in standardized vehicle crash tests. The relationship between the belt fit measured for people in driving posture and the belt fit obtained with ATDs has not been reported in the literature. The present study compares lap and shoulder belt fit data from ATDs and to a statistical estimate for drivers using age, stature, and BMI. Methods: The lap and shoulder belt fits were measured for small-female and midsize-male Hybrid-III ATDs in a laboratory mockup of a midsize sedan. A range of lower and upper belt anchorage locations were used. The ATD belt fit data were compared with predictions from a regression model developed by data from 97 men and women measured in the same driving package conditions. Humans were free to position the belt comfortably, even if the position was not optimal. Results: The measurements of the ATD belt fit were obtained and compared to the regression estimate for a driver using age, stature, and BMI as predictors. For the small female, the ATD's lap belt was placed 46 mm further forward and 12 mm lower relative to the pelvis than the regression model estimates for a driver's lap belt placement. For the midsize male, the lap portion of the belt was placed 13 mm more rearward and 33 mm lower on the physical ATD than the regression model estimates for a similarly sized driver. The shoulder belt was placed an average of 66 mm more inboard and 11 mm more outboard on the small-female and midsize-male physical ATDs, respectively, compared with regression model estimates for drivers. Conclusions: Differences in the lap and shoulder belt fits were quantified between the physical ATDs and regression predictions for similarly sized humans in driving postures. The consequences of these differences should be investigated to help increase understanding of the relationship between belt fit and belt performance.